Respuesta :

Answer:

3/2x²yz – 9/8xyz + 15/4xy = 3/2xy[xz – 3/4z + 5/2)

Step-by-step explanation:

Given 3/2x²yz – 9/8xyz + 15/4xy. Let's look for a common factor.

3/2x²yz = 3/2 * x * y * z

9/8xyz = 3/2 * 3/4 * x * y * z

15/4 = 3/2 * 5/2 * x * y

Looking at the above; 3/2, x and y are common to all terms. Therefore the factor is:

3/2xy. Now let's factor it from each term

3/2x²yz = 3/2xy(xz)

9/8xyz = 3/2xy(3/4z)

15/4xy = 3/2xy(5/2), therefore we have:

3/2x²yz – 9/8xyz + 15/4xy = 3/2xy[xz – 3/4z + 5/2).

ACCESS MORE